Association between Patient History and Physical Examination and Osteoarthritis after Ankle Sprain - van Ochten, John M.; de Vries, Anja D.; van Putte, Nienke; Oei, Edwin H.G.; Bindels, Patrick J. E.; Bierma-Zeinstra, Sita M. A.; van Middelkoop, Marienke (International Journal of Sports Medicine, 2017)
Structural abnormalities on MRI are frequent after an ankle sprain. To determine the association between patient history, physical examination and early osteoarthritis (OA) in patients after a previous ankle sprain, 98 patients with persistent complaints were selected from a cross-sectional study. Patient history taking and physical examination were applied and MRI was taken. Univariate and multivariable analyses were used to test possible associations. Signs of OA (cartilage loss, osteophytes and bone marrow edema) were seen in the talocrural joint (TCJ) in 40% and the talonavicular joint (TNJ) in 49%. Multivariable analysis showed a significant positive association between swelling (OR 3.58, 95%CI 1.13;11.4), a difference in ROM of passive plantar flexion (OR 1.09, 95%CI 1.01;1.18) and bone edema in the TCJ. A difference in ROM of passive plantar flexion (OR 1.07, 95%CI 1.00;1.15) and pain at the end range of dorsiflexion/plantar flexion (OR 5.23, 95%CI 1.88;14.58) were associated with osteophytes in the TNJ. Pain at the end of dorsiflexion/plantar flexion, a difference in ROM of passive plantar flexion and swelling seem to be associated with features of OA (bone marrow edema, osteophytes) in the TCJ and TNJ. Our findings may guide physicians to predict structural joint abnormalities as signs of osteoarthritis.Level of evidence: 1b
Keywords: ankle; injury; examination; radiographic; abnormalities